A legendary chest X-ray - Gea Nicoletti; Davide Tizzani; Paola Molino (Emergency Care Journal, 2025)
Buffalo Chest is a rare condition involving bilateral pneumothorax (PNX), either spontaneous or, more commonly, iatrogenic, due to the presence of one or more communicating pathways between the pleural cavities. It is a critical condition that clinicians must be aware of and actively investigate, as it places the patient at high risk for bilateral tension pneumothorax. The name derives from an old legend in which Native Americans were said to be able to kill a buffalo instantly with a single arrow to the chest, as it would induce bilateral tension pneumothorax. Diagnosis is based on imaging and dynamic testing. A chest X-ray typically reveals bilateral pneumothorax, while CT (Computed Tomography) allows both identification of the bilateral PNX and assessment of any communication between the two pleural spaces. However, a definitive diagnosis relies on dynamic tests demonstrating the migration of gas or contrast medium into the contralateral hemithorax after being introduced via a chest drain.